2018
DOI: 10.2147/opth.s145266
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic corneal neuropathy: clinical perspectives

Abstract: Diabetic keratopathy is characterized by impaired innervation of the cornea that leads to decreased sensitivity, with resultant difficulties with epithelial wound healing. These difficulties in wound healing put patients at risk for ocular complications such as surface irregularities, corneal infections, and stromal opacification. Pathological changes in corneal innervations in diabetic patients are an important early indicator of diabetic neuropathy. The decrease in corneal sensitivity is strongly correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 73 publications
(71 reference statements)
0
19
0
Order By: Relevance
“…Chronic hyperglycaemia leads to a variety of metabolic changes, such as the accumulation of advanced glycation end products, increased polyol pathway ux, reactive oxygen species production, as well as activation of protein kinase C pathway, causing corneal neuronal degeneration and apoptosis of neural cells [14,22]. Decreased corneal sensitivity in diabetic patients is a sign of corneal diabetic neuropathy [14,21,22]. There were made a lot of studies which showed decreased corneal sensitivity in DM patients [23][24][25][26][27][28][29] and abnormalities of corneal nerve structure [24,28,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic hyperglycaemia leads to a variety of metabolic changes, such as the accumulation of advanced glycation end products, increased polyol pathway ux, reactive oxygen species production, as well as activation of protein kinase C pathway, causing corneal neuronal degeneration and apoptosis of neural cells [14,22]. Decreased corneal sensitivity in diabetic patients is a sign of corneal diabetic neuropathy [14,21,22]. There were made a lot of studies which showed decreased corneal sensitivity in DM patients [23][24][25][26][27][28][29] and abnormalities of corneal nerve structure [24,28,[30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…These may be due to diabetic corneal neuropathy -pathological changes of corneal innervations in diabetic patients. Diabetic corneal neuropathy is a part and an important early indicator of diabetic neuropathy [21]. Chronic hyperglycaemia leads to a variety of metabolic changes, such as the accumulation of advanced glycation end products, increased polyol pathway ux, reactive oxygen species production, as well as activation of protein kinase C pathway, causing corneal neuronal degeneration and apoptosis of neural cells [14,22].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidants, such as carnosine and β-carotene, were also suggested to be beneficial for the prevention of DM-related corneal changes 106,107. Experimental treatment modalities including gene therapy, molecular, and stem cell therapies have been developed 12,55. Di et al55 recently showed that bone marrow-derived mesenchymal stem cells could attenuate excessive inflammatory responses, activate corneal progenitor cells, and enhance would healing of diabetic cornea.…”
Section: Treatment Of Anterior Segment Complicationsmentioning
confidence: 99%
“…Patients with DM demonstrate progressive decrease in corneal nerve density and reduction in corneal sensitivity,7,8 which subsequently result in the impairment of corneal epithelial wound healing process and increased susceptibility to persistent epithelial defects and corneal infections 911. These complications can potentially lead to blindness, which underscores the importance of understanding the impact of DM on anterior segment diorders 12…”
Section: Introductionmentioning
confidence: 99%
“…Corneal ectasia, a complication occurring after refractive surgery, causes progressing steepening and thinning of the cornea, and there is strong interest in understanding its risk factors [9,10]. Corneal neuropathy affects nearly 50% of patients with diabetes mellitus, a metabolic disease characterized by elevated blood glucose, which affects over 400 million people globally and over 9% of the population in the United States [11,12]. Diabetes causes a number of vascular complications, including diabetic retinopathy, the leading cause of blindness in individuals of working age in developed countries [13][14][15], and corneal neuropathy [16][17][18].…”
Section: Introductionmentioning
confidence: 99%